A Study on Elements of Machine Vision and Machine Learning in Industrial Vision Systems - Jarosław PANASIUK (jaroslaw.panasiuk@wat.edu.pl); Adrianna ADAMUS (adrianna.adamus@student.wat.edu.pl) (Problemy Mechatroniki)
The article presents an analysis of issues regarding the current state and prospects of using machine learning elements in industrial applications of vision systems. The analysis is preceded by a short introduction to the subject of machine vision as well as a presentation of the results of research on industrial 3D vision systems, leading to conclusions that affect the prospects for further development of vision systems with elements of machine learning.